"I'm not going to walk, just for the sake of walking…": a qualitative, phenomenological study on physical activity during hospital stay. Issue 1 (2nd January 2020) - Koenders, Niek; van Oorsouw, Roel; Seeger, Joost P. H.; Nijhuis – van der Sanden, Maria W. G.; van de Glind, Irene; Hoogeboom, Thomas J.
Abstract: Purpose: To understand beliefs, thoughts, attitudes, and experiences related to physical activity during hospital stay in patients and health care providers. Methods: A qualitative, interpretive, phenomenological study examined the common meaning and lived experiences of patients and health care providers related to inpatient physical activity. Data from semi-structured interviews were analysed using qualitative content analysis. Results: A total of 42 participants (18 patients and 24 health care providers) were interviewed. Patients and health care providers described physical activity as a purposeful activity to achieve a goal. In contrast, they talked about physical and mental rest to balance inpatient physical activity. Furthermore, the hospital environment was felt to discourage patients to be physically active with care centred around the hospital beds, frequent disturbances of rest on hospital rooms, and dependency of patients on health care providers as important sources. The ability of patients to perform physical activity was associated with feelings, such as freedom and autonomy. Conclusions: Physical activity during hospital stay is a purposeful activity to achieve a goal, and should be well-balanced with both physical and mental rest according to patients and health care providers. In addition, the hospital environment seems to be a source of low inpatient physical activity. Implications for rehabilitation: Health care providers should offer meaningful activities to engage patients' interest in being physically active during hospital stay. Tailored interventions aiming to increase inpatient physical activity should be balanced with phases of both physical and mental rest. A change of the hospital environment in both culture and the build environment is needed to elicit physical activity in patients during hospital stay.